INSTITUCIONALIZACIÓN DEL SERVICIO DE AGUA POTABLE EN EL SALVADOR. UNA APROXIMACIÓN HISTÓRICA A LA ADMINISTRACIÓN NACIONAL DE ACUEDUCTOS Y ALCANTARILLADOS (ANDA) - Fonseca Zúñiga, Edgardo (Universidad de Costa Rica, 2021)
The institutionalization of potable water services in El Salvador had a significant boost in 1961, with the creation of the Administración Nacional de Acueductos y Alcantarillados (ANDA). This entity was able to centralize water distribution with direct involvement of the State. Despite this, anda continues to provide its services with varying degrees of efficacy, causing an imbalance in drinking-water coverage across the country. This article aims to study the historical evolution of the aforementioned phenomenon.